2012
DOI: 10.1111/j.1365-2834.2012.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers don’t get the corner office

Abstract: The findings support those reported in the business literature that inadequate physical workspaces are counterproductive in terms of both functionality and organizational power. Suggestions are made regarding the workspace needs of first-line nurse managers, based on a closer alignment between the work environment and their role responsibilities. These findings have implications for decisions regarding organizational support of first-line nurse managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…). The visible and respected role of nursing management and leadership is important for achieving the goals of nursing (Paliadelis , Pegram et al . , Viinikainen et al .…”
Section: Introductionmentioning
confidence: 99%
“…). The visible and respected role of nursing management and leadership is important for achieving the goals of nursing (Paliadelis , Pegram et al . , Viinikainen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both quantitative and qualitative studies published in the field of nursing management have dealt with distress and suffering at work, [2,6] structural factors, [5] factors in employee attraction and retention, [7] emotional health, [9] organizational structure, [14] factors that influence the NM's practice environment, [1,3] and NMs' lack of influence at work. [17][18][19] However, none of these studies have linked these factors to QWL specifically.…”
Section: Overview Of the Scientific Literature On Qwl In The Disciplimentioning
confidence: 99%
“…They must also regularly update their professional management skills to meet ministerial and organizational requirements for optimal management of the work environment for the benefit of nursing staff, on the one hand, and of both accessibility and continuity of care and services for the benefit of the population, on the other. [21] In reviewing the scientific literature, [12][13][14][15][16][17][18][19][20] we found that a significant amount of NM time is spent on the administrative management of operations, including staff training, work schedule management, mentoring, substitutions, completion of forms of all kinds, participation in meetings, drafting of minutes, checking payroll, supervision, and mail delivery. Finally, striking a balance between their clinical and administrative roles was essential for NMs to assume their clinicaladministrative leadership within the organization.…”
Section: Nms' Scope Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In achieving this goal, the role of ward nurse managers should not be underestimated as they are in a pivotal position to increase job satisfaction of nurses (Hayes et al . ), as they are responsible for the human, physical and clinical resources of a ward or unit (Paliadelis ). Despite limited resources, ward nurse managers should ensure proactive leadership and facilitate ways to revitalize the work environment (Pietersen , Prosen ).…”
Section: Implications For Nursing Managementmentioning
confidence: 99%